In Experts, underlying processes that drive visuomotor adaptation are different than in Novices - Leukel, Christian; Gollhofer, Albert; Taube, Wolfgang (Frontiers in Human Neuroscience, 2015)
Processes responsible for improvements in motor performance are often contrasted in an explicit and an implicit part. Explicit learning enables task success by using strategic (declarative) knowledge. Implicit learning refers to a change in motor performance without conscious effort. In this study, we tested the contribution of explicit and implicit processes in a visuomotor adaptation task in subjects with different expertise in the task they were asked to adapt. Thirty handball players (Experts) and 30 subjects without handball experience (Novices) participated. Three experiments tested visuomotor adaptation of a free throw in team handball using prismatic glasses. The difference between experiments was that in Experiment 2 and 3, contribution of explicit processes was prevented, whereas Experiment 1 allowed contribution of explicit and implicit processes. Retention was assessed in Experiment 3. There were three main findings: i) contribution of explicit processes to adaptation was stronger in Experts than Novices (Experiment 1), ii) adaptation took longer in Experts when preventing contribution of explicit processes (Experiment 2) and iii) retention was stronger in Experts (Experiment 3). This study shows that learning processes involved in visuomotor adaptation change by expertise, with more involvement of explicit processes and most likely other implicit processes to adaptation in Experts.